Atividade antifúngica in vitro de compostos naftoquinoidais contra cepas de Candida tropicalis resistentes ao fluconazol - Santos Neta, Maria Adalgiza dos (2012)
The incidence of opportunistic infections caused by fungi, with emphasis on Candida species has increased substantially. Studies report that there has been a notable increase of infections by non-albicans species (Candida tropicalis, Candida glabrata, Candida parapsilosis and Candida krusei). Clinical isolates resistant to azoles, particularly fluconazole, are increasingly reported. The naphthoquinones are an important class of active molecules biologically presenting antibacterial, antifungal, antiviral, antiinflammatory, antipyretic, anti-cancer and trypanocidal and has been tested extensively in several pharmacological studies. In recent years intensified the interest in in this substances, not only due to your importance in vital biochemical processes as well as the increasing emphasis that they show in various pharmacological studies. This study aimed to evaluate and compare the effect of antifungal naphthoquinones against strains of Candida tropicalis resistant and susceptible to fluconazole, using different techniques such as broth microdilution methods, procedures Flow Cytometry procedures and Comet assay. We use seven strains of Candida tropicalis resistant to fluconazole for this study, which were isolated from blood and were part of the collection of yeasts Experimental Laboratory Bioprospecting in yeast (LABEL), affiliated with the Faculty of Pharmacy, Federal University of Ceará. We used three compounds of naphthoquinones against the seven strains of Candida tropicalis and were subjected to in vitro sensitivity tests, which showed an antifungal activity potent. Through Flow Cytometry, it was possible to assess morphological changes and membrane integrity of these compounds fronts to significant strains in addition to mitochondrial dysfunction and production of reactive oxygen species. Through the Comet assay was possible to find significant damage to DNA. In summary, the results suggest that these compounds may be used as antifungal agents for the treatment of candidemia.